Assessment of disaster waste management in NCR - Osorio, Ezra D.; Tandoc, Frederick Jaysol M.; Tanchuling, Maria Antonia N.; Diola, Ma. Brida Lea D. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Disasters create a large volume of debris and waste. It can overwhelm the solid waste management facilities and impact on other emergency response and recovery activities. If poorly managed, these wastes can have a significant impact on the environment and the public health. This study aimed to assess the disaster waste management practices in NCR in order to prepare properly and to minimize the risks, impacts, and cost effective process for the collection, transportation, storage, treatment and disposal of wastes. Review of documents, site visits and ocular inspections in seven cities (such as cities of Malabon, Manila, Marikina, Navotas, Pasig, Quezon and Taguig), coordination with stakeholders and focus group discussion, and disaster waste analysis were done to assess the disaster waste management practices in Metro Manila. Using the UNEP-OCHA as a standard in assessment of disaster waste management, it has been found out that most activities in the post-recovery and contingency phase were not practiced by the local government units. In addition, tools such as MRF and MRS map and footprint of temporary storage facilities were generated. Several guidelines were recommended to improve the current disaster waste management in Metro Manila.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Refuse and refuse disposal; Disaster waste management